(untitled) (Bangladesh Journal of Medical Science, 2014)
Kikuchi-Fujimoto Disease (KFD) present with Dysphagia, fever and lymphadenopathy. A young adult Bangladeshi female presented with fever and cervical lymphadenopathy. Broad-spectrum antibiotic (3rd generation oral cephalosporin) were given but no improvement after one month. FNAC suggested non specific lymphadenitis. Later on, excision biopsy of cervical lymph node was done and histopathology suggested KFD. Oral prednisolone was given showing improvement and no relapse was en-counted Awareness of this disorder by clinicians and pathologists will help misdiagnosis and inappropriate treatment. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18305 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.212-214